1833 Ga. Laws 226, 228, § 7 - (:unkn) unknown (General Publisher, 1833)
Prohibition for “any free person of colour” to own, use, or carry any firearms.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES